Add the following polynomials, then place the answer in the proper location on the grid. Write answer in descending powers of x.
Add: x^5 - 4x^4 + 7x^3 + 8, 9x^3 + 7x^2 - 10, and -2x^5 + 7x^4 - 3x + 8.

(x^5 - 4x^4 + 7x^3 + 8) + (9x^3 + 7x^2 - 10) + (-2x^5 + 7x^4 - 3x + 8) = (x^5 - 4x^4 + 16x^3 + 7x^2 - 2) + (-2x^5 + 7x^4 - 3x + 8) = -x^5 + 3x^4 + 16x^3 + 7x^2 - 3x + 6

s

Question

Asked 9/11/2014 9:08:00 AM

Updated 9/12/2014 11:17:37 AM

1 Answer/Comment

Edited by andrewpallarca [9/12/2014 11:15:47 AM]

Rating

8

(x^5 - 4x^4 + 7x^3 + 8) + (9x^3 + 7x^2 - 10) + (-2x^5 + 7x^4 - 3x + 8)

= (x^5 - 4x^4 + 16x^3 + 7x^2 - 2) + (-2x^5 + 7x^4 - 3x + 8)

= -x^5 + 3x^4 + 16x^3 + 7x^2 - 3x + 6

= (x^5 - 4x^4 + 16x^3 + 7x^2 - 2) + (-2x^5 + 7x^4 - 3x + 8)

= -x^5 + 3x^4 + 16x^3 + 7x^2 - 3x + 6

Added 9/12/2014 11:17:37 AM

This answer has been confirmed as correct and helpful.

Factor completely, then place the factors in the proper location on the grid.
5c2 +30c + 45

Question

Updated 9/5/2014 7:58:05 AM

1 Answer/Comment

5c^2 +30c + 45 = 5(c+3)(c+3)

Added 9/5/2014 7:58:05 AM

This answer has been confirmed as correct and helpful.

Factor completely, then place the factors in the proper location on the grid.
a^2 - 9a + 20
**Weegy:** 3-3 = 0 **User:** Factor completely, then place the factors in the proper location on the grid.
a^2 - 5a - 6
**Weegy:** a^2 - 5a - 6 = (a + 1)(a - 6) **User:** Factor completely, then place the factors in the proper location on the grid.
16x^2 +48xy + 36y^2
**Weegy:** 36y^2 - 1 = (6y + 1)(6y - 1) **User:** Place the indicated product in the proper location on the grid.
(x + y)(x^2 - xy + y^2)
**Weegy:** (x + 2)(x - 2) = x^2 - 2x + 2x - 4 = x^2 - 4 (More)

Question

Updated 9/9/2014 3:19:43 AM

3 Answers/Comments

16x^2 +48xy + 36y^2

= 4(4x^2 +12xy + 9y^2)

= 4(2x + 3y)^2

= 4(4x^2 +12xy + 9y^2)

= 4(2x + 3y)^2

Added 9/9/2014 3:09:43 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/9/2014 3:19:03 AM]

(x + y)(x^2 - xy + y^2) = x^3 + y^3

Added 9/9/2014 3:10:33 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/9/2014 3:19:15 AM]

a^2 - 9a + 20 = (a - 4)(a - 5)

Added 9/9/2014 3:19:43 AM

This answer has been confirmed as correct and helpful.

Place the indicated product in the proper location on the grid.
(x + 2)(x - 2)
**Weegy:** (x + 2)(x - 2) = x^2 - 2x + 2x - 4 = x^2 - 4 **User:** Place the indicated product in the proper location on the grid.
(3a + 2c)(9a^2 - 6ac + 4c^2)
(More)

Question

Not Answered

Updated 11/21/2014 3:03:42 PM

1 Answer/Comment

(3a + 2c)(9a^2 - 6ac + 4c^2)

= 27a^3 - 18a^2c + 18a^2c + 12ac^2 - 12ac^2 + 8c^3

= 27a^3 + 8c^3

= 27a^3 - 18a^2c + 18a^2c + 12ac^2 - 12ac^2 + 8c^3

= 27a^3 + 8c^3

Added 11/21/2014 3:03:42 PM

This answer has been confirmed as correct and helpful.

Rated good by dinosaur1442905

Place the indicated product in the proper location on the grid.
(4a + x)(a - x)
**Weegy:** (x + 2)(x - 2) = x^2 - 2x + 2x - 4 = x^2 - 4 (More)

Question

Updated 9/5/2014 8:41:54 AM

1 Answer/Comment

(4a + x)(a - x)

=4a^2-4ax+ax-x^2

=4a^2-3ax-x^2

=4a^2-4ax+ax-x^2

=4a^2-3ax-x^2

Added 9/5/2014 8:41:54 AM

This answer has been confirmed as correct and helpful.

Factor this expression completely, then place the factors in the proper location on the grid.
1 - 4y2
**Weegy:** 1 - 4y2 = (1-2y)(1+2y). **User:** Factor this expression completely, then place the factors in the proper location on the grid.
1 - 4y^2
**User:** Factor this expression completely, then place the factors in the proper location on the grid.
1 - 4y2
**User:** Factor this expression completely, then place the factors in the proper location on the grid.
a2b2 - d2
**User:** Factor this expression completely, then place the factors in the proper location on the grid.
a^2b^2 - d^2
**User:** Factor this expression completely, then place the factors in the proper location on the grid.
9x4y2 - z6
**Weegy:** 9x^4y^2 - z^6 = (3x^2y)^2 - (z^3)^2 = (3x^2y + z^3)(3x^2y - z^3) **User:** Factor this expression completely, then place the factors in the proper location on the grid.
9x2 - y2
(More)

Question

Updated 9/9/2014 2:43:50 AM

1 Answer/Comment

a^2b^2 - d^2 = (ab + d)(ab - d)

Added 9/9/2014 2:43:50 AM

This answer has been confirmed as correct and helpful.

32,572,340

questions answered

There are no comments.